R&D spending, competitive advantage, and firm performance in Thailand - Krittiga Insee; Muttanachai Suttipun (Cogent Business & Management, 2023)
The study aims to examine the relationship between R&D spending and firm performance and to test for the mediator effect of competitive advantage on the relationship between R&D spending and firm performance of private firms in Thailand. By collecting data from the sample with a questionnaire from 151 private companies in Thailand. This study's main objectives are to examine the relationship between R&D spending competitive advantage and firm performance. The research data is tested and analyzed by the structure equation model. As the results, the study found that even though R&D spending do not directly have relationship with firm performance, there is a positive relationship between R&D spending and firm performance mediated by competitive advantage of private firms in Thailand. For contribution and implication, the evidence of this study points out that competitive advantage is an important variable that will enhance the efficiency of firm performance measured by balanced scorecard from corporate R&D spending. Moreover, resource-based theory can be demonstrated to explain the relationship between R&D spending, competitive advantage, and corporate performance in Thailand as well as other countries.
Keywords: M40; M41; M48; 650; competitive advantage; firm performance; R&D spending; Thailand